PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI SUKU DINAS PENDIDIKAN WILAYAH I JAKARTA SELATAN - Adhysta Prima Sandi; Dodi Prasada (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the influence of the work environment and work motivation on employee performance in the South Jakarta Region I education sub-department. The method used is quantitative. The sampling technique used saturated sampling and obtained 65 respondents. Data analysis uses coefficient tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination, and hypothesis testing. The results of this research are that the influence of the work environment on employee performance in the South Jakarta Region I education sub-department is significant on employee performance with a coefficient of determination of 75.4% and the hypothesis test obtained t count > t table or (14.944 > 1.994). Work motivation has a significant effect on employee performance with a coefficient of determination value of 72.9% and hypothesis testing obtained t count > t table (14.024 > 1.994). The work environment and work motivation simultaneously have a significant effect on employee performance with the regression equation Y= 5.307 + 0.427X1 + 0.333 X2. The coefficient of determination value is 77.8% while the remaining 22.2% is influenced by other factors. Hypothesis testing obtained calculated f value > f table or (126.110 > 3.120).